The Perception of Ageism, Generativity, and the Attainment of Developmental Tasks of Elderly Widowers and Widows in Bogor, West Java, Indonesia - Bona Intan Rahmaniah; Diah Krisnatuti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
In every stage of human lives as well as later adulthood (elderly), there are developmental tasks to be attained and demand the elderly to adapt to various changes both from the internal and external environment. The aim of this research was to analyze the influence of ageism and generativity on the developmental task of elderly widower and widow. The cross-sectional study was used as the design of this research. The research was conducted in Empang Village, South Bogor Sub-District and West Cilendek Village, West Bogor Sub-District, Bogor City. As many as 60 persons were involved as research sample, consisted of 30 elderly widowers and 30 elderly widows which were chosen by snow-ball techniques. The result showed that there was no significant difference in developmental task of elderly widower and widow. The category of ageism was low while generativity and developmental task were moderate. There were significant positive correlations and influences of the length of education and generativity on developmental tasks of elderly widower and widow.